2016
DOI: 10.1016/j.stueduc.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the learning environment, learning preferences, and approaches to studying among medical students in Pakistan

Abstract: Students at a Pakistani medical college were surveyed using instruments taken from Western research. The students who rated their courses positively tended to adopt an organised approach in their learning and studying. The students who perceived that their assessment and workload were inappropriate preferred a transmissive approach to teaching and adopted a surface approach in their learning and studying. The students who preferred a student-centred approach to teaching tended to adopt a deep approach in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
9
0
2
Order By: Relevance
“…To achieve these skills learning environment, learning styles and approaches of learners play a significant role. 11,13 In our study female predominance was observed. Majority having done their intermediate concurrent to a study conducted in Karachi.…”
Section: Discussionsupporting
confidence: 55%
“…To achieve these skills learning environment, learning styles and approaches of learners play a significant role. 11,13 In our study female predominance was observed. Majority having done their intermediate concurrent to a study conducted in Karachi.…”
Section: Discussionsupporting
confidence: 55%
“…Rote memorization is commonly seen. Hence, students use their notes and study guides to prepare for exams (Ullah et al, 2016). This leads to surface learning instead of an in-depth understanding of concepts and underlying principles (Getha-Eby et al, 2014).…”
Section: Lack Of Research Trainingmentioning
confidence: 99%
“…Pre and post test study can be carried out to measure the learning approaches in a specific subject with the help of single teaching strategy i;e: PBL and type of assessment; as assessment drives student learning. 22 Assessment enables us to measure time to time outcomes and changes in learning approaches. Moreover, PBL teaching strategies should be integrated in dental curriculum of BUMDC to enhance critical thinking.…”
Section: Recommendationsmentioning
confidence: 99%
“…7 In Pakistan, most of the undergraduate medical and dental institutes have the hybrid traditional curriculum. 22 Bahria University Medical and Dental College (BUMDC) is practicing hybrid curriculum which is modular in nature. Hybrid curriculum is the amalgamation of teacher centered and student centered educational content.…”
mentioning
confidence: 99%